Digitalisation and Sales: A study on the impact of online platforms on the retail sector - Majola, Mnqobi Kwanda (The IIE, 2021)
In the modern day retail sector the increased incorporation of technology into daily operating processes of brands and businesses has made it easier for consumers and brands to interact with each other. However, this has also provided a market for counterfeiters to thrive in, especially in a post Coronavirus world where countless brands and industries have fully embraced a move to a more online based form of operations, the process of digitalisation was expedited as a result of the pandemic. As a result, it has become difficult for South African consumers to authenticate products they purchase online and ensure they are receiving the expected quality product for the amount of money they pay and put strain on the reliability and trustworthiness of online marketplaces. This paper seeks to investigate the impact that these digital processes have had on consumer trust and loyalty, but also looking into how counterfeiters have an impact on the credibility of big name brands, such as Nike, in a South African context. The study was conducted by incorporating a qualitative data collection method, making use of online focus group discussions as these allowed the researcher to a hold an open forum on which participants could openly and anonymously share their views and experiences with online marketplaces and how these have impacted their purchasing behaviours going forward, the result of these discussions was a main recurring theme which indicated trust was seen as a higher order factor for online purchases.
Keywords: Technology; Post-COVID-19; Brand trust; Brand loyalty; Purchasing behaviour; Counterfeit